Passive victims or active agents : a case study of Indonesian female marriage migrants in Singapore - Koh, Dorcas Jia Hui. (2013)
Marriages that cross the borders of nation states have become increasingly common. This trend of cross-border marriages can also be observed in Singapore. This research paper seeks to gain a greater understanding of the experiences of the Indonesian foreign brides in Singapore. In order to do so, this paper adopts an agency approach, and attempts to listen to the stories and experiences of the Indonesian foreign brides in Singapore. This paper will first examine the motivations for marriage migration of the Indonesian foreign brides. It will then discuss the difficulties and challenges faced by the foreign brides in Singapore, and the strategies used by the Indonesian foreign brides to resist, negotiate and challenge their relatively disadvantaged position, both in society and their families. The paper will then conclude with an analysis of the Indonesian female marriage migrants interactions with the legal structures that have been put in place.